Targets for Neoadjuvant Therapy – The Preferences of Patients with Early Breast Cancer - Thill, M.; Pisa, G.; Isbary, G. (Geburtshilfe und Frauenheilkunde, 2016)
Background: Therapists and administrative bodies consider a pathological complete remission as an independent and relevant endpoint in evaluations of the clinical utility of neoadjuvant therapy for early breast cancer. The present study aims to investigate which treatment outcomes of a neoadjuvant therapy are considered by the patients themselves to be relevant. Materials and Methods: With the help of analytic hierarchy process (AHP) methods patient preferences about the treatment targets of neoadjuvant therapy were assessed quantitatively. All participants had undergone a neoadjuvant therapy in the form of chemotherapy and, in HER2-positive cases, as a targeted antibody therapy against HER2 for the primary diagnosis of early breast cancer 12–36 months prior to the interview. The criteria for the hierarchy model were identified in an earlier qualitative survey. The patient interviews were conducted by 4 experienced female interviewers. Results: Forty-one patients participated in the quantitative survey, of these 15 (36.6 %) had suffered from HER2-positive disease. The achievement of pCR was the most important therapeutic target for the patients, even before disease-free survival, overall survival and the option for breast-preserving operation. Avoidance of side effects was considered to be the least important. In a comparison of the side effects the patients judged fatigue to be most important before nausea and loss of hair. Conclusion: For the patients the achievement of a pathological complete remission is considered to be an independent, relevant and highly desired target of neoadjuvant therapy.
Keywords: early breast cancer; neoadjuvant; chemotherapy; pathological complete remission (pCR); patient preference